A construção curricular na perspectiva freireana: um estudo de caso na Escola Municipal Santa Rita, na cidade de Diadema-SP - Abensur, Patricia Lima Dubeux (2009)
This study is a part of national research being carried out under the auspices of Paulo Freire s Chair at PUC-SP and supervised by Dra. Ana Maria Saul. The objective is to analyze the contribution and the influence of Paulo Freire s theory on the Brazilian Public Education System from the nineties until now. In order to achieve the objectives, this work combines a qualitative approach and a case study, incorporating the contributions of an ethnographic work to describe and analyze the ordinary life of a school in the municipality of Diadema-SP, focusing on the developing process of the school curriculum. Besides the observations, which are the natural tools of data collection, this research uses semi-structured interviews and analysis of documents. The data collection, analysis and results are divided into four thematic sections related to Paulo Freire s definitions during his period of management as the Secretary of Education in the Municipality of São Paulo (1989-1991). The themes are: collective construction, respect for the principle of school autonomy, the value of theory-practice unit and the permanent development of educational professionals. During the analysis the three themes were developed. Collective construction presented an improvement relating to the participation and the communication that exists between the various levels and the different players in constructing the curriculum. Autonomy of the school improved its way to develop plans and projects; permanent development of educational professionals allowed for the professors' reflections on their practices. The data showed that the value of the theory-practice unit has many challenges to face. However, the school studied and the municipality of Diadema represent a significant challenge when it comes to defining a public school that combines democracy with quality